Photoimmunotherapy-Induced Pyroptosis Remodels the Microenvironment to Enhance Cancer Immunotherapy - Zhang, Wenqiao; Yuan, Haitao; Wang, Peili; Yi, Letai; Wen, Qinglian; Zhou, Runhua; Bai, Yunmeng; Ma, Jingbo; Wang, Xiaoxian; Liang, Yanting; Liang, Zhen; Peng, Xin; et al. (ACS materials letters, 2024)
Immunosuppressive tumor microenvironment (TME) and immune escape are the main reasons that make immunotherapy ineffective and even hinder tumor progression. Immunogenic cell death (ICD) based on pyroptosis stands up as an ideal strategy to overcome the TME and achieve satisfactory antitumor effects. In addition, the insight into activation of the cGAS-STING pathway afford an efficient means to enhance the antitumor immune effect. Hence, we report a tumor treatment strategy based on photosensitizer PDI-mediated photoimmunotherapy that enhances immunogenic pyroptosis by synergistically activating the cGAS-STING pathway of macrophages. In vitro and in vivo studies showed that this light-activated immunotherapy could stimulate a strong antitumor immune response and achieve good antitumor efficacy in combination with immune checkpoint inhibitors. Our work sheds light on developing photoimmunotherapy to improve the immunosuppressive tumor microenvironment and simultaneously promote immune-mediated tumor regression.